Next Generation Passive Optical Networks: A Futuristic Approach - Vikas Sharma, Sharad Sharma (International Journal of Advanced Science and Technology, 2020)
This paper shows the evolution of a passive optical network with different optical networks. This paper shows that the different types of access networks their classifications and their different types of passive optical networks. This paper tells how networks differ from cooper networks to optical networks. This also shows that the difference between active and passive optical networks and different passive optical networks. This paper shows that the analysis of the different passive optical network and shows the different parameters of the different types of passive optical networks. The passive optical network is the better option for the access network because it is cheaper and the future of the optical communication as compare to the active network. This paper is to know about the meaning of passive optical networks and its architecture. It explains the different types of passive optical networks and their uses for the present as well as the future of the communication. Passive optical networks provide a huge bandwidth for the data transmission for triple-play (video-voice-data) simultaneously. The requirement for high-speed communication networks is the high bandwidth for data transmission without interruption. Passive optical networks provide this facility very effectively.